Tanggap pertumbuhan dan perkembangan tanaman tomat (solanum lycopersicum) terhadap paklobutrazol dan komposisi media tanam (Response of the growth and development of tomato plants (solanum lycopersicum) on paclobutrazol and the composition of the planting media) - Maudi Siti Sarah Nazibah; Karno Karno; Dwi Retno Lukiwati (Journal of Agro Complex, 2018)
The objective of this research was to study the response of tomato plant on paclobutrazol and different planting media composition. The study used Completely Randomized Design factorial 4x3with the first factor wasapplication of paclobutrazol 0 ppm (P0), 50 ppm (P1), 100 ppm (P2), dan 150 ppm (P3), and the second factor was composition of planting media (soil:compost) 80%:20% (M1), 60%:40% (M2), dan 40%:60% (M3),with 3 replications. The parameters observed were plant height, number of leaves, number of flowers, leaf chlorophyll content, number of fruit. Data were subjected to analysis of variance and further test by Duncan's Multiple Range Test (DMRT). The results showed that the application of paclobutrazol doses 50, 150 ppm, and without paclobutrazol (control) resulted in the number of flower of 70.56, leaf chlorophyll content index of 53.16, and plant height of 157.78 cm that ware significantly higher (p<0.05) than other treatments. The treatment without paclobutrazol with 60%:40% planting composition resulted in a significantly higher (p<0.05) leaf number than other treatments. Paclobutrazol doses of 100 ppm and 60%:40% of planting media composition yielded 10.33 fruitsthat was higher (p<0.05) than other treatments. Keywords : Paclobutrazol, planting composition, tomato, growth